Italy's Post-COVID-19 Stroke Network: Has It Returned to Pre-Pandemic Standards? - Erika Kacerik; Francesca Bottega; Aida Andreassi; Giuseppe Sechi; Alberto Zoli; Marco Botteri; Carlo Signorelli; Nazzareno Fagoni (MDPI AG, 2024)
The COVID-19 pandemic strongly transformed the healthcare system in the Lombardy region (Italy), forcing a rapid reorganization of hospital structures. The emergency medical service (EMS) system and emergency departments (EDs) were among the most affected departments. Several studies have shown a change in the epidemiology of time-dependent pathologies, such as stroke, during the pandemic's peak. However, there is little scientific evidence regarding the interpandemic phase. The regional register for ED accesses (EUOL) was analyzed, taking into consideration all accesses for stroke and stroke-like syndromes during the years 2019, 2020, and 2021. The analysis shows a significant difference in the average number of diagnoses per month [2092 vs. 1815 vs. 2015, respectively (p < 0.05)] and an increase in the percentage of transports carried out by EMS vehicles to EDs [17% vs. 25% vs. 22%, respectively (p < 0.05)]. The length of stay (LOS) increased for both discharged patients (9.0 vs. 10.1 vs. 11.2 h, respectively; p < 0.005) and hospitalized patients (7.5 vs. 9.7 vs. 10.6 h, respectively; p < 0.005). During the COVID-19 pandemic, the overall number of stroke diagnoses decreased, while the percentage of patients transported to EDs by EMS vehicles increased. Furthermore, an increased processing time in EDs was highlighted.